Комптонiзацiя космiчного мiкрохвильового випромiнювання холодним ультрарелятивiстським електрон-позитронним вiтром та природа ∼130 ГeВ лiнiй - Iakubovskyi, D.; Yushchenko, S. (Publishing house "Academperiodika", 2019)
Previously, an astrophysical explanation of the narrow gamma-ray line-like feature(s) at ∼100 GeV from the Galactic Center region observed by Fermi/LAT [2] was proposed in [1]. The model of [1] is based on the inverse Compton scattering of external ultraviolet/X-ray radiation by a cold ultrarelativistic e+-e− pulsar wind. We will show that the extra broad ∼30 MeV component should arise from the Comptonization of cosmic microwave background radiation. We estimate the main parameters of this component and show that it can be detectable with MeV telescopes such as CGRO/COMPTEL. The location of the CGRO/COMPTEL unidentified source GRO J1823-12 close to the excess of the 105–120-GeV emission (Region 1 of [2]) can be interpreted as an argument in favor of the astrophysical model of the narrow feature(s) at ∼100 GeV.